Vegetation and soil seed bank relationships across microhabitats in an abandoned Quercus suber parkland under simulated fire (Ecoscience, 2012)
Mediterranean agro-forestry systems are undergoing rapid change due to abandonment. This turns formerly cultivated or grazed oak-tree parklands (i.e., savanna-type formations called “dehesas”) into flammable formations of scattered trees within a matrix of shrubs with open spaces. Wildfires can now occur, threatening the persistence of these formations. Fire-prone shrublands commonly regenerate after fire from seeds stored in the soil. Understanding the relationships between standing vegetation and the soil seed bank across microhabitats can help predict the response of the system in case of fire. Here we investigated these relationships in an abandoned Quercus suber (cork oak) dehesa in central Spain. Vegetation and soil were sampled and assigned to different microhabitats: under the trees (TRC), in dense shrub cover (DSC), and in low shrub cover (LSC). A heat shock was applied to half of each sample to simulate fire; the other half served as control. Both sets of samples were then germinated in a greenhouse. Almost 90% of the species were herbs, while the rest were woody shrubs. The number of species recorded in TRC and DSC was lower than in LSC, in which species richness, particularly herbs, was maximal. Heating increased the total number of species that germinated, but mean species richness per sample was not altered. Heating markedly increased the number of germinations in all microhabitats, particularly those of woody species. Furthermore, the germination of shrubby species increased in the 3 microhabitats, notably in TRC. While the standing plant community was well differentiated among microhabitats, this was not the case for the soil seed bank, which was homogeneous across microhabitats, with or without heating. We conclude that the high density of shrubby seeds found in TRC or in the other microhabitats presents substantial threats to the persistence of Q. suber parklands in case of fire.

Mediterranean pine and oak distribution in southern Spain: Is there a mismatch between regeneration and adult distribution? (Journal of Vegetation Science, 2011)
Questions: What is the current distribution of pine and oak species along environmental gradients in southern Spain? Do pine and oak regeneration niches differ from the environmental niches of adults? Is oak species regeneration favoured under the canopy of pine forests? Location: Forest areas of Andalusia (∼87 600 km2, southern Spain). Methods: We compiled extensive forest inventory data to explore differences in abundance (basal area, m2 ha−1) patterns of adults (dbh >7.4 cm) and regeneration (dbh ≤7.4 cm) of five pine and five oak species. Canonical correspondence analysis (CCA) and generalized linear models were applied to explore species–environment relationships along climatic, edaphic, topographic and fire-frequency gradients. Results: Both pines and oaks segregated along complex environmental gradients, with pines generally dominating in more severe (colder and drier) environments, while oaks dominated in milder, wetter winter areas. In 40-55% of mature pine stands there was a lack of regeneration in the understorey, while in two oak species (Q. suber and Q. canariensis) 70% of stands did not show regeneration. Pine recruits were found at a higher frequency and abundance under the canopy of their congeners, whereas some oaks (Q. ilex) had greater regeneration under mixed pine–oak canopies. Conclusions: Climatic limitations and soil properties partly explained the regional distribution of pines and oaks. We found evidence for an upward shift of Q. ilex recruits towards areas with colder conditions in pine forests, which could be explained by a possible facilitative effect of the pine canopy on seedling establishment.

Seed removal in two coexisting oak species: ecological consequences of seed size, plant cover and seed-drop timing (Oikos, 2008)
Seed predation and dispersal can critically influence plant community structure and dynamics. Inter-specific differences arising at these early stages play a crucial role on tree recruitment patterns, which in turn could influence forest dynamics and species segregation in heterogeneous environments such as Mediterranean forests. We investigated removal rates from acorns set onto the ground in two coexisting Mediterranean oak species –Quercus canariensis and Q. suber– in southern Spain. We developed maximum likelihood estimators to investigate the main factors controlling probabilities of seed removal and to describe species-specific functional responses. To account for inter-specific differences in seed-drop timing, two experiments were established: a simultaneous exposure of acorns of the two species (synchronous experiments) and a seed exposure following their natural seed-drop phenology (diachronic experiments). A total of 1536 acorns were experimentally distributed along a wide and natural gradient of plant cover, and removal was periodically monitored for three months at two consecutive years (with contrasting differences in seed production and thus seed availability on the ground). The probability of seed removal increased with plant cover (leaf area index, LAI) for the two oak species. Inter-specific differences in acorn removal were higher in open areas and disappeared in closed microhabitats, especially during a non-mast year. Despite later seed-drop, Q. suber acorns were removed faster and at a higher proportion than those of Q. canariensis. The higher probability of seed removal for this species could be attributed to its larger seed size compared to Q. canariensis, as inter-specific differences were less pronounced when similar sized acorns were exposed. Inter-specific differences in seed removal, arising from seed size variability and microsite heterogeneity, could be of paramount importance in oak species niche separation, driving stand dynamics and composition along environmental gradients.

Soil water content and emergence time control seedling establishment in three co-occurring Mediterranean oak species (Canadian Journal of Forest Research, 2008)
Tree species can differ in their responses to resource availability during the critical phase of establishment, which could influence forest dynamics. In Mediterranean forests, most of the attention has focused on the effects of shade and summer drought on seedling survival, but little is known about the effect of autumn to spring rains on earlier stages of recruitment. A sowing experiment was set up along natural light and water gradients with three co-occurring oak species (Quercus suber L. (cork oak), Quercus canariensis Willd. (Algerian oak), and Quercus pyrenaica Willd. (Pyrenean oak)) that show limited natural regeneration in southern Spain. Recruitment stages were monitored for 1 year. Models of seed germination, seedling emergence, and seedling survival as well as of overall recruitment patterns were developed as functions of light, soil moisture, and soil compaction. The influence of intraspecific variation in seed mass and emergence time were also tested. Excess soil water levels during the winter reduced germination and emergence and lengthened time to emergence (in waterlogged open areas), which in turn decreased seedling survival during the dry season. Seedlings from larger seeds were more likely to germinate and emerge. The results suggest that temporal and spatial variability of soil water content, mediated by emergence time and seed size, play a crucial role in the regeneration dynamics of Mediterranean oak forests.
doi: 10.1139/X08-089